2000
DOI: 10.1080/002073900412598
|View full text |Cite
|
Sign up to set email alerts
|

Using computer software in the teaching of mechanics

Abstract: The paper looks at ways of using computer software in the teaching of mechanics. The various reasons for using software are discussed to justify the use of software. A number of examples are then considered to show how diå erent types of software can be used. Examples shown are taken from very speci® c types of software, more general simulation software and mathematical software. The paper discusses using software to explore mechanics, to challengè misconceptions' , to make links between mathematical represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the other hand, when the graphical skills of the experimental group were compared with the pre-test and post-test point average, it was observed that VL applications also improved the skills of drawing, understanding and interpreting graphics. The graphical representation of the interactive physics program used in this study is quite good (Graham & Rowlands, 2000). Students have converted the virtually obtained data into graphical form using appropriate buttons and menus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the graphical skills of the experimental group were compared with the pre-test and post-test point average, it was observed that VL applications also improved the skills of drawing, understanding and interpreting graphics. The graphical representation of the interactive physics program used in this study is quite good (Graham & Rowlands, 2000). Students have converted the virtually obtained data into graphical form using appropriate buttons and menus.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group students used Interactive Physics simulation program to perform experiments (www.design-simulation.com/IP/). This simulation and modelling software is an environment in which almost every physical state can be reconstructed and tracked, and it can provide excellent visual images with numerical, graphical or vector representations (Graham & Rowlands, 2000). Interactive physic is software that is widely used in the world that can easily develop course material without knowing any programming languages.…”
Section: Vl Activitiesmentioning
confidence: 99%
“…[1][2][3][4] One reason for this is the changing syllabus of mathematics and physics A level, meaning many students are poorly prepared for courses on engineering mathematics and dynamics at university. [2] It has also been identified that many students have misconceptions about areas of mechanics that prevent students from moving onto more advanced concepts.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It has also been identified that many students have misconceptions about areas of mechanics that prevent students from moving onto more advanced concepts. Examples being the mistaken belief that the resultant force on a projectile must be aligned with the direction of motion, [3] and the reason a full can rolls down a slope in a 'race' with an empty can is to do with the extra mass rather than the distribution of mass. [3] In mechanics, there is an opportunity to build teaching tools, where the equations of motion are solved within a mathematical package such as MATLAB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation